Pelaksanaan Perubahan Hak Guna Bangunan yang Dibebani Hak Tanggungan Menjadi Hak Milik Untuk Rumah Tinggal - Komang Adhi Kresna Purnama; I Nyoman Alit Puspadma; Ni Gusti Ketut Sri Astiti (Jurnal Konstruksi Hukum, 2021)
This study aims to analyze the implementation of changes in building use rights that are encumbered with mortgages to property rights for households and to explain legal protection for creditors whose objects of collateral have been encumbered with Mortgage Rights are requested to change from Building Use Rights to Property Rights. The research method used in this research is normative legal research with a statute approach and a case approach. Data sources are primary and secondary legal materials which are analyzed qualitatively. Data processing is carried out by describing and describing all legal materials as a result of document studies and interviews enhanced by literature study and study of applicable provisions. The results of this study indicate that the implementation of changes in building use rights to property rights in the Land Office is processed in accordance with the provisions of the Regulation of the State Minister for Agrarian Affairs / Head of the National Land Agency Number 5 of 1998 concerning Changes in Building Use Rights or Right to Use Land for Residential Land with Mortgage Rights become Property Rights. These changes can be made at the request of the right holder with written approval from the holder of the Mortgage along with a Certificate of Mortgage at the Land Office where the object of the Mortgage is located and for the implementation of changes in building use rights that are still burdened with the Mortgage Right to Ownership Rights have legal consequences that the Mortgage Rights the person concerned becomes erased (void) as stated in the provisions of article 18 paragraph (1) letter d of the UUHT but does not cause the guaranteed debt to be written off.